1991
DOI: 10.1104/pp.97.4.1342
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Induction of Salicylic Acid Accumulation in Cucumber after Inoculation with Pseudomonas syringae pv syringae

Abstract: Inoculation of one true leaf of cucumber (Cucumis sativus L.) plants with Pseudomonas syringae pathovar syringae results in the systemic appearance of salicylic acid in the phloem exudates from petioles above, below, and at the site of inoculation. Analysis of phloem exudates from the petioles of leaves 1 and 2 demonstrated that the earliest increases in salicylic acid occurred 8 hours after inoculation of leaf 1 in leaf 1 and 12 hours after inoculation of leaf 1 in leaf 2. Detaching leaf I at intervals after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
249
1
7

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 468 publications
(273 citation statements)
references
References 17 publications
16
249
1
7
Order By: Relevance
“…However, the concentration of SA used in this study is not necessarily unphysiological if compared to the concentration of several 100 pM SA reported in petiole exudates from Pseudomonas-syringae-infected cucumber (Rasmussen et al, 1991) or the 8-pg total SNfresh mass reported from l? syringae infected A. thaliana (Lawton et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…However, the concentration of SA used in this study is not necessarily unphysiological if compared to the concentration of several 100 pM SA reported in petiole exudates from Pseudomonas-syringae-infected cucumber (Rasmussen et al, 1991) or the 8-pg total SNfresh mass reported from l? syringae infected A. thaliana (Lawton et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cucumber plants inoculated on one leaf with the HR-causing pathogen Pseudomonas syringae pv. syringae accumulated high levels of SA in phloem exudates even when the inoculated leaf remained on the plant for only 6 h (Rasmussen et al, 1991). Maximal levels of SA were measured 18 h after inoculation in this system, so the majority of systemically accumulating SA was not synthesized by the inoculated leaf.…”
mentioning
confidence: 92%
“…Although the advantages of Arabidopsis as a genetic tool are well documented, the cucumber system offers several advantages for the biochemical study of SAR. First and most importantly, the mobile signal for SAR is produced by cucumber leaves within 6 h after inoculation with incompatible bacteria, providing a narrow time frame within which to look for an active compound (Rasmussen et al, 1991;Smith et al, 1991). Second, the large leaves of cucumber are easy to saturate with inoculum and produce correspondingly large amounts of mobile signal.…”
mentioning
confidence: 99%
“…Research into the possible systemic signals responsible for initiating acquired resistance has suggested salicylic acid (SA) to be a likely candidate. Exogenous application of SA induces PR protein gene expression in tobacco (Ward et aL, 1991), cucumber (Metraux et aL, 1990) and Arabidopsis thafiana (Uknes et al, 1993b); whilst endogenous SA levels rise locally around lesions following pathogen attack in tobacco (Malamy et al, 1990;Enyedi et aL, 1992), Arabidopsis thaliana (Uknes et al, 1993b) and also in cucumber, where SA levels were observed to rise in phloem exudates (Metraux et aL, 1990;Rasmussen et al, 1991).…”
Section: Introductionmentioning
confidence: 99%